Naphthoquinone based chemosensor 2-(2 `-aminoethylpyridine)-3-chloro-1,4-naphthoquinone: detection of metal ions, X-ray -crystal structures and DFT studies - Patil, Amit; Ware, Anuja P.; Bhand, Sujit; Chakravarty, Debamitra K.; Gonnade, Rajesh G.; Pingale, Subhash S.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2016)
Naphthoquinone based Chemosensor 2; 2-(2'-aminoethylpyridine)-3-chloro-1,4-napthoquinone have been synthesized and characterized. Chemosensor 2 crystallizes in the orthorhombic space group Pbcn and shows extensive intramolecular as well as intermolecular hydrogen bonding interactions. Each molecule of Chemosensor 2 showed interaction with five neighboring molecules via C-H center dot center dot center dot N, N-H center dot center dot center dot N, C-H center dot center dot center dot Cl and C-H center dot center dot center dot O interactions. Slipped pi-pi stacking interaction was observed in adjacent quinonoid and benzenoid rings. Chemosensor abilities of Chemosensor 2 ligand have been evaluated with metal ions viz. Cu2+, Ni2+, Zn2+, Co2+, Fe3+, Mn2+, Cr3+, Hg2+, La3+ and Cd2+ in methanol, methanol-water mixture and in presence of mild base triethylamine. Stoichiometry of Chemosensor 2 with metal ions such as Cu2+, Ni2+, Zn2+ and Co2+ ions was determined by Jobs method in methanol and were found as 1:1 for Cu2+ and 2:1 for Ni2+, Zn2+ Co2+. The variation in the metal ligand ratio is observed in aqueous media for Cu2+. Chemosensor 2 can be used selectively for naked eye detection of Cu2+ ions. The association constant obtained in methanol shows the trend Cu2+>Ni2+>Co2+. Cu2+ and two (Ni-1 and Ni-2) Ni2+ complexes were synthesized. Ni-2 complex showed coordination of Chemosensor 2 ligands was through pyridine nitrogen's only. The Chemosensor 2 and its deprotonated forms in methanol, water and triethylamine were also studied by TD-DFT studies. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Chemosensor; hydrogen bonding; Naphthoquinone; pi-pi stacking; TD-DFT

Binding selectivity of vitamin K3 based chemosensors towards nickel(II) and copper(II) metal ions - Patil, Amit; Lande, Dipali N.; Nalkar, Archana; (Gejji, Shridhar P.; Chakrovorty, Debamitra; Gonnade, Rajesh; Moniz, Tania; Rangel, Maria; Pereira, Eulalia; Salunke-Gawali, Sunita (Journal of molecular Structure, 2017)
The vitamin K3 derivatives 2-methyl-3-[(pyridin-2-ylmethyl)-amino]-1,4-naphthoquinone (M-1), 2-methyl-3-[(pyridin-2-ylethyl)-amino]-1,4-naphthoquinone (M-2), 2-methyl-3-((2-(thiophen-2-yl) methyl)amino)naphthalene-1,4-dione (M-3) and 2-methyl-3-((2-(thiophen-2-yl)ethyl)amino)naphthalene-1,4-dione (M-4) have been synthesized, characterized and studied for their chemosensor abilities towards transition metal ions. Crystal structures of M-1 to M-4 revealed a variety of N-H center dot center dot O, C-H center dot center dot center dot O, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions. Minor variations in such interactions by chemical stimuli such as metal ions, results in change in color that can be visualized by naked eyes. It has been shown that electronic structure and H-1 NMR, vibrational as well as electronic spectra from the density functional theory agree well with the experiments. The metal ion binding in ethanol, ethanol-water and in mild base triethylamine brings forth recognizing ability of M-1 toward Ni2+ whereas M-2 exhibits large sensing ability for Cu2+ ion. Interestingly M-1 display varying metal ion binding specificity in different solvents with the association constant in ethanol being 11,786 M-1 for Ni2+ compared to 9462 M-1 for the Cu2+. A reversal in preferential binding of M-2 with the respective association constants being 4190 M-1 and 6370 M-1 is discernible. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone Molecular-structures; Anthraquinone; Aqueous-solution; Chemosensor; Crystal-structures; Cu(II); Derivatives; DFT; Fluorometric Chemosensors; hydrogen bonding; Naphthoquinone; pi-pi stacking; Recognition; sensors